Influence of short-term growth on mechancial risk indicators in female gymnasts - Wyatt, H.; Gittoes, M.; Irwin, G. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Female gymnasts have increased vulnerability to chronic injuries during heightened growth. The study aimed to further understanding of the influence of growth rate and morphological growth rate on mechanical risk indicators over a 12 month period. Biomechanical measurements were taken during the performance of handstand and forward walkover skills at three time points. Bicristal to biacromial ratio measurements informed the division of the gymnasts into `high` and `low` growth groups. Greater mean mechanical risk indicator differences were found when the cohort was divided according to morphological growth rate. Large effects ( >.14) were found between time points for 88% of mechanical risk indicators. The importance of the shape and size of growth, along with the value of longitudinal monitoring of gymnasts was subsequently emphasised.